2022
DOI: 10.3389/fnbeh.2022.961070
|View full text |Cite
|
Sign up to set email alerts
|

The influence of mindfulness-based interventions on the academic performance of students measured by their GPA. A systematic review and meta-analysis

Abstract: Objective: Mindfulness-based interventions are increasingly used in health, economic and educational systems. There are numerous studies demonstrating the effectiveness of mindfulness-based interventions in the educational sectors (primary, secondary, and tertiary). This systematic review and meta-analysis assessed the current state of research on the effectiveness of mindfulness-based interventions on the academic performance of students as measured by their grade point average (GPA).Methods: Literature searc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 54 publications
0
3
0
Order By: Relevance
“…A recent study revealed that an MBSR intervention group showed statistically signifcantly fewer symptoms of stress and distress and had higher mindfulness than the control group. Previous studies of MBSR have emphasized its potential benefts for university students, such as minimizing perceived stress, preserving emotional stability, enhancing social functioning, and increasing the self-attractiveness of the group [14][15][16][17]. Tis study adopted the Cochrane systematic review method to assess the efect of psychological interventions and the overall impact of MBSR treatment on the psychological condition of university students, aiming to provide a scientifc basis for the clinical practice of MBSR treatment.…”
Section: Introductionmentioning
confidence: 99%
“…A recent study revealed that an MBSR intervention group showed statistically signifcantly fewer symptoms of stress and distress and had higher mindfulness than the control group. Previous studies of MBSR have emphasized its potential benefts for university students, such as minimizing perceived stress, preserving emotional stability, enhancing social functioning, and increasing the self-attractiveness of the group [14][15][16][17]. Tis study adopted the Cochrane systematic review method to assess the efect of psychological interventions and the overall impact of MBSR treatment on the psychological condition of university students, aiming to provide a scientifc basis for the clinical practice of MBSR treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Trait mindfulness (also known as "dispositional mindfulness") is amongst the most important personality traits for meditation-and mindfulness-based interventions (25). It is characterized by sustained, non-judgmental attention to the present moment (26) and provides a pivotal resource in cognitive control and emotional regulation (27,28). Consequently, the nuanced interplay between health behaviours and academic performance may be significantly influenced by individual differences in trait mindfulness.…”
Section: Introductionmentioning
confidence: 99%
“…Like most skills, mindfulness improves with practice, and students who are trained for mindfulness skills can better focus on their tasks or lessons. Mindfulness can help students improve their reading habits and planning skills (12). Studies have shown a significant positive relationship between mindfulness and academic performance, noting that mindfulness can improve learners' academic performance (11,13).…”
Section: Introductionmentioning
confidence: 99%